2016
DOI: 10.1051/0004-6361/201527577
|View full text |Cite
|
Sign up to set email alerts
|

Solar irradiance observations with PREMOS filter radiometers on the PICARD mission: In-flight performance and data release

Abstract: Context. The PREcision Monitoring Sensor (PREMOS) is a solar radiometer on board the French PICARD mission that was launched in June 2010 and decommissioned in April 2014. Aims. The PREMOS radiometer obtains solar irradiance measurements in specific spectral windows in the UV, visible, and nearinfrared. In this paper, the PREMOS data and calibration methods are presented. Methods. Using back-up channels, the degradation can theoretically be assessed to correct operational channels. However, a strong degradatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 44 publications
1
8
0
Order By: Relevance
“…Some deviation after, however, can be seen in the 210 nm channel after May 2012 and in the 215 nm channel from early 2013 onward. At 210 nm Cessateur et al [2016] find a similar deviation when comparing the PREMOS data with SORCE/SOLSTICE (see their Figure 13). We emphasize here that for the comparison shown in Figure 5 both data sets are in absolute values, and both the PREMOS channels and the SOLID composite are not detrended; i.e., they include the long-term trend.…”
Section: Validation Of Ssi Compositesupporting
confidence: 59%
See 1 more Smart Citation
“…Some deviation after, however, can be seen in the 210 nm channel after May 2012 and in the 215 nm channel from early 2013 onward. At 210 nm Cessateur et al [2016] find a similar deviation when comparing the PREMOS data with SORCE/SOLSTICE (see their Figure 13). We emphasize here that for the comparison shown in Figure 5 both data sets are in absolute values, and both the PREMOS channels and the SOLID composite are not detrended; i.e., they include the long-term trend.…”
Section: Validation Of Ssi Compositesupporting
confidence: 59%
“…For that period, the SOLID composite compares well with the observations made by the PREcision Monitoring Sensor [Schmutz et al, 2009] on board the PICARD mission [Thuillier et al, 2006]. Figure 5 shows the SOLID composite convolved with the broadband filters of the PREMOS instrument and the PREMOS observations [Cessateur et al, 2016] centered at 210 nm (left) and 215 nm (right). The agreement between both time series for the two wavelength channels is excellent.…”
Section: Validation Of Ssi Compositementioning
confidence: 72%
“…We already compared the operational SORCE (Béland et al, 2013) data to V2 OMI irradiances, finding a good match between the detrended short-term variability patterns (Marchenko et al, 2016). Finally, we incorporate all the available measurements from the PREcision Monitoring Sensor (PREMOS) on board the PICARD mission (Cessateur et al, 2016). We also use the Global Ozone Monitoring Experiment-2 (GOME-2A: Munro et al, 2016), additionally corrected for the instrument degradation (https://www.eumetsat.int/website/home/TechnicalBulletins/GOME2/DAT_3036881.html).…”
Section: The Datamentioning
confidence: 99%
“…The correction proves to be quite adequate on a short-term basis, nevertheless severely limiting use of the GOME-2A data on the solar cycle time frame. Finally, we incorporate all the available measurements from the PREcision Monitoring Sensor (PREMOS) on board the PICARD mission (Cessateur et al, 2016). This particular mission, though relatively short term (June 2010 to April 2014), provides a broad wavelength coverage that is important for our validation effort.…”
Section: The Datamentioning
confidence: 99%
“…Up to 250 nm, a clear solar minimum is shown on 10 January 2009 (within a few days). However, in the EUV, the minimum found by SolACES 47 is a few months earlier (August 2008). The early 2009 date of minimum is roughly consistent with the study by 48 that found a date of late 2008 for the minimum in TSI, Mg II, and F10.7.…”
Section: Resultsmentioning
confidence: 97%